1997
DOI: 10.1084/jem.185.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ATP Diphosphohydrolase Activity with Endothelial Cell Activation

Abstract: Quiescent endothelial cells (EC) regulate blood flow and prevent intravascular thrombosis. This latter effect is mediated in a number of ways, including expression by EC of thrombomodulin and heparan sulfate, both of which are lost from the EC surface as part of the activation response to proinflammatory cytokines. Loss of these anticoagulant molecules potentiates the procoagulant properties of the injured vasculature. An additional thromboregulatory factor, ATP diphosphohydrolase (ATPDase; designated as EC 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
233
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(241 citation statements)
references
References 48 publications
8
233
0
Order By: Relevance
“…Such circumstances are frequently encountered in small arteries where platelet interactions with the vessel wall are dependent mainly on collagen and the von Willebrand factor (38) during such clinical interventions as angioplasty, where deep injury of the vessel wall often results in vascular reocclusion (39). In addition, platelet interactions with the vessel wall are mostly dependent on extracellular nucleotides and are regulated by the presence of ectonucleotidases, among which, CD39, the ATP diphosphohydrolase, has proved to be of major importance (40,41). Moreover, besides fibrin deposition in multiple organs because of deficiency in vascular protective effects, CD39 knock-out mice display an unexpected prolongation of the bleeding time because of selective desensitization of the P2Y 1 receptor (41).…”
Section: Discussionmentioning
confidence: 99%
“…Such circumstances are frequently encountered in small arteries where platelet interactions with the vessel wall are dependent mainly on collagen and the von Willebrand factor (38) during such clinical interventions as angioplasty, where deep injury of the vessel wall often results in vascular reocclusion (39). In addition, platelet interactions with the vessel wall are mostly dependent on extracellular nucleotides and are regulated by the presence of ectonucleotidases, among which, CD39, the ATP diphosphohydrolase, has proved to be of major importance (40,41). Moreover, besides fibrin deposition in multiple organs because of deficiency in vascular protective effects, CD39 knock-out mice display an unexpected prolongation of the bleeding time because of selective desensitization of the P2Y 1 receptor (41).…”
Section: Discussionmentioning
confidence: 99%
“…The dual nature of ectoenzymes also needs to be rigorously tested, because some of their functions seem to perform independently of their enzymatic activity [106,110]. It is feasible that the large extracellular domains of ectoenzymes and their association with other membrane proteins or components can mediate responses without involvement of their catalytic activity [110].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the failure to develop specific inhibitors remains a major impediment to ongoing new discoveries on NTPDase activity [106]. Recently, it was demonstrated that P2 receptor antagonists inhibited human and plasma membrane bound NTPDases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations